Spray drying for the encapsulation of oils—a review - Mohammed, Nameer Khairullah; Tan, Chin Ping; Abd Manap, Yazid; Muhialdin, Belal J.; Meor Hussin, Anis Shobirin (MDPI AG, 2020)
The application of the spray drying technique in the food industry for the production of a broad range of ingredients has become highly desirable compared to other drying techniques. Recently, the spray drying technique has been applied extensively for the production of functional foods, pharmaceuticals and nutraceuticals. Encapsulation using spray drying is highly preferred due to economic advantages compared to other encapsulation methods. Encapsulation of oils using the spray drying technique is carried out in order to enhance the handling properties of the products and to improve oxidation stability by protecting the bioactive compounds. Encapsulation of oils involves several parameters—including inlet and outlet temperatures, total solids, and the type of wall materials—that significantly affect the quality of final product. Therefore, this review highlights the application and optimization of the spray drying process for the encapsulation of oils used as food ingredients.